Cement-based self-leveling material based on shield muck fully-recycled sand powder as well as preparation method and application of cement-based self-leveling material
Recycling sand powder for shield residue mud, and used it to prepare the cement base self -leveling material, solve the problem of the traditional self -level material consumption of natural resources, and realize the efficient resource of shield slag soil. Utilize and improve material performance.
Patent Information
- Application Number
- CN202411475083.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-28
AI Technical Summary
The fine aggregates used in traditional self-leveling materials mainly come from river sand, quartz sand and machined sand, which leads to high consumption of natural resources, high cost, and difficulty in effectively utilizing engineering waste.
Through the processing of watering, drying and screening of shield residue mud to recover sand powder, it is used to prepare the cement -based self -flowing material to reduce the dependence on traditional fine aggregate.
The efficient resource utilization of shield slag is realized, the consumption of river sand, quartz sand, and mechanism sand is reduced, the production cost is reduced, and the liquidity and strength of the material is improved.
Smart Images

Figure BDA0005095860560000071 
Figure BDA0005095860560000081 
Figure BDA0005095860560000082
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a cement-based self-leveling material based on fully recycled sand powder from shield slag, and a preparation method and application thereof. Background Art
[0002] With the rapid development of rail transit, the amount of slag generated by shield tunnel construction is also increasing year by year. Relevant data show that my country currently discharges more than 2 billion tons of engineering waste mud and slag each year, accounting for more than 60% of the total construction waste. According to statistics, the amount of residual mud and slag generated by my country's subway projects has rapidly increased from 160,000 cubic meters in 1965 to 68.82 million cubic meters in 2018, and is expected to exceed 200 million cubic meters by 2030. However, most of the residual mud and slag have not been reasonably and effectively utilized. Judging from the disposal situation in major cities in my country, more than 80% of the residual mud and slag are mainly landfilled, and only less than 20% of the residual mud and slag are used for engineering and mountain landscaping. It is estimated that the land area occupied by residual mud and slag landscaping in 2017 alone was close to 20 square kilometers. Therefore, the research on efficient resource utilization technology of engineering residual mud and slag has great practical engineering needs and important social and environmental effects.
[0003] Cement-based self-leveling material is a mortar made by mixing cement as a gelling material, adding suitable additives, fine sand and fillers. In dry mixes, fine aggregate is the main component and its demand is huge. However, the fine aggregate used in traditional self-leveling materials mainly comes from river sand, quartz sand and machine-made sand, which consumes a lot of natural resources. In order to protect the ecological environment, the mining of river sand is restricted, and the price of quartz sand is relatively expensive. The production of machine-made sand mainly depends on the mining and crushing of natural rocks or ores. Although this process can produce sand materials that meet certain standards, it also consumes natural resources, and the production process has high energy consumption. With the increasing attention paid to the resource utilization of construction waste in my country, the engineering community has an increasing demand for alternative solutions to reduce the use of these materials, so as to reduce engineering costs and reduce the consumption of sand resources. In CN111875318A, fly ash is used as the main raw material, and refractory brick crushing is used as aggregate to prepare self-leveling mortar, which reduces the use of river sand, increases the working performance and strength of the material, and reduces the shrinkage of the material. However, the above method has the following shortcomings: 1) The requirements for the main fly ash consumed are high, and the fly ash used is Grade I fly ash, which is the highest quality and the smallest proportion of fly ash, and other fly ash with larger volume and lower quality is not consumed; 2) The sand particle size in the material ratio is large, and the fluidity of the self-leveling material is relatively poor; 3) The mortar is relatively high in the material ratio, and the material itself reflects the performance of the mortar, which will also cause the material cost to be too high, and there are deficiencies in economy. CN114853435A provides a cement mortar grouting material prepared by magic crystal powder, which has a relatively low mortar and has good working performance, but has the following shortcomings: 1) The strength is relatively low; 2) The requirements for sand are high, and fine sand in natural river sand is used; 3) The cost is relatively high; 4) There are multiple liquid materials in the material ratio of this method, which is very inconvenient in storage, transportation and use on the construction site.
[0004] The present invention develops a self-leveling material based on fully recovered sand powder from shield engineering slag sludge and a preparation method thereof. The recovered sand powder is obtained by subjecting shield engineering slag sludge to water washing, drying, screening and other process treatments. Since shield engineering slag sludge has the characteristics of large mud content and fine particle size, it has been difficult to effectively utilize it, and its disposal faces problems such as high cost, environmental pollution, and occupation of land resources. The present invention innovatively proposes to use sand recovered from slag for self-leveling materials. The prepared material has stable performance. This process realizes the reuse of fine-grained slag, which is not only low in price and widely available, but also reduces the exploitation and consumption of natural resources such as river sand, quartz sand, and machine-made sand, and has significant environmental and socio-economic benefits. Summary of the invention
[0005] In response to the above-mentioned existing technical problems, the present invention provides a cement-based self-leveling material based on fully recycled sand powder from shield slag, and a preparation method and application thereof. The cement-based self-leveling material has good fluidity, tensile bonding strength and stability, and its impact resistance and compressive and flexural strength all meet the requirements of the specifications. At the same time, the technology of the present invention greatly reduces the dependence on river sand, quartz sand and machine-made sand, reduces costs, and realizes efficient resource utilization of engineering slag, while ensuring that the obtained self-leveling material meets the main performance index requirements of the specifications.
[0006] In the first aspect, the present invention provides a cement-based self-leveling material based on fully recycled sand powder from shield tunneling slag. The raw materials of the cement-based self-leveling material based on fully recycled sand powder from shield tunneling slag include cement, fly ash, silica fume, water reducer, cellulose ether, rubber powder, accelerator and recycled sand powder, calculated by weight.
[0007] Furthermore, the raw materials of the cement-based self-leveling material based on fully recycled sand powder from shield slag include, by weight: 470-510 parts of cement, 130-160 parts of fly ash, 10-30 parts of silica fume, 1-3 parts of water reducer, 1-3 parts of cellulose ether, 10-20 parts of glue powder, 1-3 parts of accelerator and 600-800 parts of recycled sand powder.
[0008] Furthermore, the mud content of the recovered sand powder is ≤10%, the particle size range of the recovered sand powder is 0.075-2.36 mm, and the mass proportion of the recovered sand powder below 0.15 mm is ≥65%.
[0009] Furthermore, the cement is silicate cement, and the cement grade is not less than 42.5R.
[0010] Furthermore, the fly ash is Class II fly ash.
[0011] Furthermore, the silica fume grade is not lower than SF92.
[0012] Furthermore, the water reducer is a polycarboxylate water reducer, preferably polycarboxylate water reducer 325C, in powder form.
[0013] Furthermore, the cellulose ether is hydroxypropyl methylcellulose.
[0014] Furthermore, the rubber powder is redispersible latex powder.
[0015] Furthermore, the coagulant is selected from one or more of lithium carbonate, lithium hydroxide, lithium chloride, aluminum sulfate, and sodium aluminate;
[0016] Preferably, the coagulant is sodium aluminate (CAS number is 11138-49-1).
[0017] Furthermore, the raw materials of the cement-based self-leveling material based on fully recycled sand powder from shield slag of the present invention may also include an expansion agent and a defoaming agent.
[0018] Furthermore, the expansion agent is selected from one or more of plastic expansion agent, calcium sulfoaluminate, calcium oxide, and magnesium oxide;
[0019] Preferably, the expansion agent is magnesium oxide.
[0020] Furthermore, the defoamer is a polyether defoamer, preferably a DF65 defoamer.
[0021] Furthermore, the raw materials of the cement-based self-leveling material based on fully recycled sand powder from shield slag include, by weight: 470-510 parts of cement, 130-160 parts of fly ash, 10-30 parts of silica fume, 0.1-50 parts of expansion agent, 1-3 parts of water reducer, 0.1-1 part of defoaming agent, 1-3 parts of cellulose ether, 10-20 parts of rubber powder, 1-3 parts of accelerator and 600-800 parts of recycled sand powder.
[0022] Furthermore, the recycled sand powder in the raw material of the cement-based self-leveling material based on fully recycled sand powder from shield slag of the present invention comes from the residual mud of shield slag at the rail transit construction site, and the specific preparation steps include:
[0023] (1) Remove large rocks, metal impurities and fine sand from the shield slag and mud at the rail transit construction site through water washing and screening, and then perform coarse screening to remove organic impurities, isolated rocks and other large rocks;
[0024] (2) washing the shield slag screened in step (1) with water, and controlling the washing time according to the mud content of the shield slag, so that the surface of the sand powder at the discharge port is relatively clean and has no obvious mud marks;
[0025] (3) drying the sand powder after washing in step (2) until the water content is less than 10%, thereby achieving good dispersibility;
[0026] (4) The sand powder dried in step (3) is sieved, and the aperture of the sieve is 2.36 mm, and the middle section (particle size is less than 2.36 mm and the mud is washed away) of the sand powder is obtained, that is, the recovered sand powder.
[0027] Furthermore, the water washing in step (2) adopts a sand washing machine, including but not limited to impeller sand washing machine and other equipment.
[0028] Furthermore, the drying step in step (3) includes but is not limited to natural drying or drying in a drum dryer.
[0029] Furthermore, the screening equipment in step (4) includes but is not limited to a vibrating screen machine, etc.
[0030] In a second aspect, the present invention also provides a method for preparing a cement-based self-leveling material based on fully recovered sand powder from shield slag, comprising the following steps:
[0031] S1. Mix and stir the raw materials except the recycled sand powder according to the proportion, and the stirring time is 1 to 2 minutes;
[0032] S2. Then, the recovered sand powder is added to step S1 and stirred for 4 to 6 minutes to obtain a cement-based self-leveling material based on fully recovered sand powder from shield slag.
[0033] In the third aspect, the present invention also provides a construction method of a cement-based self-leveling material based on fully recycled sand powder from shield construction waste, wherein the cement-based self-leveling material based on fully recycled sand powder from shield construction waste is mixed and stirred with water in a mass ratio of (1400-1800): (380-420) and then constructed.
[0034] The present invention proposes to prepare a self-leveling material based on fully recycled sand powder instead of cement, fly ash, silica fume, expansion agent, water reducing agent, defoaming agent, cellulose ether, rubber powder, coagulant, recycled sand powder and water as main raw materials. Cement is used as a cementitious material, recycled sand powder is used as fine aggregate, and fly ash is used as a filler to improve the fluidity of the self-leveling material, enhance its density, and effectively inhibit the shrinkage and cracking of concrete. Secondly, the large specific surface area of fly ash can increase cohesion and water retention to prevent segregation and bleeding. An appropriate amount of silica fume can play a role in physical filling and promoting the hydration of cementitious materials. Water reducing agent, rubber powder, coagulant, expansion agent, cellulose ether, etc. are added to improve the fluidity, bonding strength, strength, shrinkage performance and water retention of the material.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) The self-leveling material based on fully recycled sand powder of the present invention meets the main physical and mechanical performance requirements of self-leveling mortar, with a 28d compressive strength of ≥6.0MPa and a 1d flexural strength of ≥2.0MPa;
[0037] (2) The self-leveling material based on fully recycled sand powder of the present invention uses polycarboxylic acid water reducer, fly ash, silica fume, water reducer and other materials to improve the fluidity and stability of the self-leveling material in the shaping stage. The slurry meets the requirement of fluidity greater than 130 mm.
[0038] (3) The self-leveling material based on fully recycled sand powder of the present invention uses an expansion agent and the like to control the dimensional change rate between -0.15 and +0.15h, which is beneficial to reduce the risk of cracking of the self-leveling mortar.
[0039] (4) The tensile bonding strength of the self-leveling material based on fully recycled sand powder of the present invention is ≥1.0 MPa, which is beneficial to prevent hollowing, cracking and falling off of the bonding interface under the action of tensile stress caused by various deformations.
[0040] (5) The present invention makes full use of fully recovered sand powder, which can reduce the consumption of natural sand, quartz sand and machine-made sand, and can not only realize the efficient and high value-added resource utilization of engineering slag and residual mud, but also reduce the consumption of natural resources and reduce costs, thus having good environmental and socio-economic benefits. DETAILED DESCRIPTION
[0041] The experimental methods in the following examples of the present invention, where no specific conditions are specified, are usually carried out under conventional conditions or under conditions recommended by the manufacturers. The various commonly used chemical reagents used in the examples are all commercially available products.
[0042] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0043] The terms "including" and "having" and any variations thereof of the present invention are intended to cover non-exclusive inclusions. For example, a process, method, device, product or equipment comprising a series of steps is not limited to the listed steps or modules, but may optionally include steps not listed, or may optionally include other steps inherent to these processes, methods, products or equipment.
[0044] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0045] The present invention is further described in the following examples, but the examples are not intended to limit the scope of protection of the present invention.
[0046] The raw materials and sources in the embodiments of the present invention are specifically as follows:
[0047] The cement used was P·Ⅱ42.5R silicate cement produced by China Resources Cement (Pingnan) Co., Ltd.; the fly ash used was Class CⅡ fly ash produced by Wushigang Co., Ltd. in Qujiang District, Shaoguan City; the silica fume used was provided by Guangdong Gatechi New Materials Technology Co., Ltd.; the expansive agent used was the high-performance concrete magnesium oxide expansive agent produced by Jiangsu Subote New Materials Co., Ltd.; the water reducer used was Sika polycarboxylate water reducer 325C, powder; the defoamer used was DF65 model defoamer produced by Chongqing Haiyu Chemical Products Co., Ltd.; the cellulose ether used was PL600 hydroxypropyl methylcellulose produced by Chongqing Pengkai Fine Chemical Co., Ltd.; the rubber powder used was Hydetech 3068 redispersible latex powder produced by Wacker Chemical (China) Co., Ltd.; and the coagulant used was sodium aluminate (CAS number 11138-49-1).
[0048] Example 1 Preparation of cement-based self-leveling material based on fully recovered sand powder from shield slag
[0049] The raw material formula of the cement-based self-leveling material based on fully recycled sand powder from shield slag in this embodiment is shown in Table 1:
[0050] Table 1: Raw material formula of cement-based self-leveling material based on fully recycled sand powder from shield slag
[0051] Raw material ingredients Content (mass parts) cement 490 Fly ash 147 Silica Fume 21 Bulking Agent 42 Water reducing agent 2.1 Defoaming agent 0.35 Cellulose ether 2.1 Rubber powder 14 Coagulant 2.1 Recycled sand powder 700
[0052] The preparation process of the recovered sand powder is:
[0053] (1) Remove large rocks, metal impurities and fine sand from the shield slag and mud at the rail transit construction site through water washing and screening, and then perform coarse screening to remove organic impurities, isolated rocks and other large rocks;
[0054] (2) washing the shield slag screened in step (1) with an impeller sand washer, and controlling the washing time according to the mud content of the shield slag so that the surface of the sand powder at the discharge port is relatively clean and has no obvious mud marks;
[0055] (3) drying the sand powder after washing in step (2) by natural air drying or using a drum dryer until the water content is less than 10%, thereby achieving good dispersibility;
[0056] (4) The sand powder dried in step (3) is sieved by a vibrating sieve method, the aperture of the sieve is 2.36 mm, and the middle section (particle size is less than 2.36 mm and the mud is washed away) sand powder is obtained, that is, the recovered sand powder, the mud content of the recovered sand powder is ≤10%, the particle size range of the recovered sand powder is 0.075 to 2.36 mm, and the mass proportion of the recovered sand powder below 0.15 mm is ≥65%.
[0057] The preparation steps of the cement-based self-leveling material based on fully recycled sand powder from shield slag in this embodiment are as follows:
[0058] S1. Mix and stir cement, fly ash, silica fume, expansion agent, water reducing agent, defoamer, cellulose ether, rubber powder and accelerator powder according to the proportion, and the stirring time is 1 to 2 minutes;
[0059] S2. Then, the recovered sand powder is added to step S1 and stirred for 4 to 6 minutes to obtain a cement-based self-leveling material based on fully recovered sand powder from shield slag.
[0060] The construction method of the cement-based self-leveling material based on fully recovered sand powder from shield slag in this embodiment is as follows:
[0061] Add water (399 parts by mass) to the cement-based self-leveling material based on fully recycled sand powder from shield slag, mix slowly for 1 minute, stop stirring, scrape off the uneven mixture on the stirring blade and the wall of the material pot with a scraper within 30 seconds, then stir quickly for 60 seconds, stop for 60 seconds, and continue to stir at high speed for 15 seconds. If there are bubbles in the mixture, stop for 60 seconds to defoam it, and then immediately put it into the mold.
[0062] Example 2 Preparation of cement-based self-leveling material based on fully recovered sand powder from shield slag
[0063] The raw material formula of the cement-based self-leveling material based on fully recycled sand powder from shield slag in this embodiment is shown in Table 2:
[0064] Table 2: Raw material formula of cement-based self-leveling material based on fully recycled sand powder from shield slag
[0065] Raw material ingredients Content (mass parts) cement 490 Fly ash 160 Silica Fume 8 Bulking Agent 42 Water reducing agent 2.1 Defoaming agent 0.35 Cellulose ether 2.1 Rubber powder 14 Coagulant 2.1 Recycled sand powder 700
[0066] The preparation process of the recovered sand powder is:
[0067] (1) Remove large rocks, metal impurities and fine sand from the shield slag and mud at the rail transit construction site through water washing and screening, and then perform coarse screening to remove organic impurities, isolated rocks and other large rocks;
[0068] (2) washing the shield slag screened in step (1) with an impeller sand washer, and controlling the washing time according to the mud content of the shield slag so that the surface of the sand powder at the discharge port is relatively clean and has no obvious mud marks;
[0069] (3) drying the sand powder after washing in step (2) by natural air drying or using a drum dryer until the water content is less than 10%, thereby achieving good dispersibility;
[0070] (4) The sand powder dried in step (3) is screened by a vibrating sieve method, the aperture of the sieve is 2.36 mm, and the middle section (particle size is less than 2.36 mm and the mud is washed away) sand powder is obtained, that is, the recovered sand powder. The mud content of the recovered sand powder is ≤10%, and the particle size range of the recovered sand powder is 0.075 to 2.36 mm, of which the mass proportion of the recovered sand powder below 0.15 mm is ≥65%.
[0071] The preparation steps of the cement-based self-leveling material based on fully recycled sand powder from shield slag in this embodiment are as follows:
[0072] S1. Mix and stir cement, fly ash, silica fume, expansion agent, water reducing agent, defoamer, cellulose ether, rubber powder and accelerator powder according to the proportion, and the stirring time is 1 to 2 minutes;
[0073] S2. Then, the recovered sand powder is added to step S1 and stirred for 4 to 6 minutes to obtain a cement-based self-leveling material based on fully recovered sand powder from shield slag.
[0074] The construction method of the cement-based self-leveling material based on fully recovered sand powder from shield slag in this embodiment is as follows:
[0075] Add water (399 parts by mass) to the cement-based self-leveling material based on fully recycled sand powder from shield slag, mix slowly for 1 minute, stop stirring, scrape off the uneven mixture on the stirring blade and the wall of the material pot with a scraper within 30 seconds, then stir quickly for 60 seconds, stop for 60 seconds, and continue to stir at high speed for 15 seconds. If there are bubbles in the mixture, stop for 60 seconds to defoam it, and then immediately put it into the mold.
[0076] Example 3 Preparation of cement-based self-leveling material based on fully recovered sand powder from shield slag
[0077] The raw material formula of the cement-based self-leveling material based on fully recycled sand powder from shield slag in this embodiment is shown in Table 3:
[0078] Table 3: Raw material formula of cement-based self-leveling material based on fully recycled sand powder from shield slag
[0079]
[0080]
[0081] The preparation process of the recovered sand powder is:
[0082] (1) Remove large rocks, metal impurities and fine sand from the shield slag and mud at the rail transit construction site through water washing and screening, and then perform coarse screening to remove organic impurities, isolated rocks and other large rocks;
[0083] (2) washing the shield slag screened in step (1) with an impeller sand washer, and controlling the washing time according to the mud content of the shield slag so that the surface of the sand powder at the discharge port is relatively clean and has no obvious mud marks;
[0084] (3) drying the sand powder after washing in step (2) by natural air drying or using a drum dryer until the water content is less than 10%, thereby achieving good dispersibility;
[0085] (4) The sand powder dried in step (3) is screened by a vibrating sieve method, the aperture of the sieve is 2.36 mm, and the middle section (particle size is less than 2.36 mm and the mud is washed away) sand powder is obtained, that is, the recovered sand powder. The mud content of the recovered sand powder is ≤10%, and the particle size range of the recovered sand powder is 0.075 to 2.36 mm, of which the mass proportion of the recovered sand powder below 0.15 mm is ≥65%.
[0086] The preparation steps of the cement-based self-leveling material based on fully recycled sand powder from shield slag in this embodiment are as follows:
[0087] S1. Mix and stir cement, fly ash, silica fume, expansion agent, water reducing agent, defoamer, cellulose ether, rubber powder and accelerator powder according to the proportion, and the stirring time is 1 to 2 minutes;
[0088] S2. Then, the recovered sand powder is added to step S1 and stirred for 4 to 6 minutes to obtain a cement-based self-leveling material based on fully recovered sand powder from shield slag.
[0089] The construction method of the cement-based self-leveling material based on fully recovered sand powder from shield slag in this embodiment is as follows:
[0090] Add water (399 parts by mass) to the cement-based self-leveling material based on fully recycled sand powder from shield slag, mix slowly for 1 minute, stop stirring, scrape off the uneven mixture on the stirring blade and the wall of the material pot with a scraper within 30 seconds, then stir quickly for 60 seconds, stop for 60 seconds, and continue to stir at high speed for 15 seconds. If there are bubbles in the mixture, stop for 60 seconds to defoam it, and then immediately put it into the mold.
[0091] Example 4 Preparation of cement-based self-leveling material based on fully recovered sand powder from shield slag
[0092] The raw material formula of the cement-based self-leveling material based on fully recycled sand powder from shield slag in this embodiment is shown in Table 4:
[0093] Table 4: Raw material formula of cement-based self-leveling material based on fully recycled sand powder from shield slag
[0094]
[0095]
[0096] The preparation process of the recovered sand powder is:
[0097] (1) Remove large rocks, metal impurities and fine sand from the shield slag and mud at the rail transit construction site through water washing and screening, and then perform coarse screening to remove organic impurities, isolated rocks and other large rocks;
[0098] (2) washing the shield slag screened in step (1) with an impeller sand washer, and controlling the washing time according to the mud content of the shield slag so that the surface of the sand powder at the discharge port is relatively clean and has no obvious mud marks;
[0099] (3) drying the sand powder after washing in step (2) by natural air drying or using a drum dryer until the water content is less than 10%, thereby achieving good dispersibility;
[0100] (4) The sand powder dried in step (3) is screened by a vibrating sieve method, the aperture of the sieve is 2.36 mm, and the middle section (particle size is less than 2.36 mm and the mud is washed away) sand powder is obtained, that is, the recovered sand powder. The mud content of the recovered sand powder is ≤10%, and the particle size range of the recovered sand powder is 0.075 to 2.36 mm, of which the mass proportion of the recovered sand powder below 0.15 mm is ≥65%.
[0101] The preparation steps of the cement-based self-leveling material based on fully recycled sand powder from shield slag in this embodiment are as follows:
[0102] S1. Mix and stir cement, fly ash, silica fume, water reducing agent, cellulose ether and rubber powder according to the proportion, and the stirring time is 1 min;
[0103] S2. Then, the recovered sand powder is added to step S1 and stirred for 4 to 6 minutes to obtain a cement-based self-leveling material based on fully recovered sand powder from shield slag.
[0104] The construction method of the cement-based self-leveling material based on fully recovered sand powder from shield slag in this embodiment is as follows:
[0105] Add water (420 parts by mass) to the cement-based self-leveling material based on fully recycled sand powder from shield slag, mix slowly for 1 minute, stop stirring, scrape off the uneven mixture on the stirring blade and the wall of the material pot with a scraper within 30 seconds, then stir quickly for 60 seconds, stop for 60 seconds, and continue to stir at high speed for 15 seconds. If there are bubbles in the mixture, stop for 60 seconds to defoam it, and then immediately put it into the mold.
[0106] Test Example 1: Performance test of cement-based self-leveling material based on fully recycled sand powder from shield slag
[0107] Part I. Test methods
[0108] The construction performance of the cement-based self-leveling material based on fully recycled sand powder from shield slag prepared in Examples 1 to 4 was tested. The specific test indicators included fluidity test, tensile bond strength test, and dimensional change rate. The test method referred to the specification JC / T985-2017 "Cement-based self-leveling mortar for ground use".
[0109] Part II: Performance Test Results
[0110] According to the test method in the first part, the performance test results are shown in Table 5;
[0111] Table 5: Construction performance test results of cement-based self-leveling materials based on fully recycled sand powder from shield slag prepared in Examples 1 to 4
[0112]
[0113] It can be seen from the performance test results in Table 5 that the cement-based self-leveling material based on fully recycled sand powder from shield slag used in Examples 1 to 4 of the present invention has a fluidity of 130 mm and above, good workability, spreading ability and surface quality, can meet the requirements of flatness and aesthetics, and has good consolidation strength, 1d compressive strength ≥ 2MPa, 28d compressive strength ≥ 6MPa, and meets the main physical and mechanical performance requirements of the self-leveling material; the present invention improves the tensile bonding strength of the self-leveling material by adopting a certain amount of redispersible latex powder and recycled sand powder, and improves the dimensional change rate of the self-leveling material by adopting a certain amount of expansion agent or reducing the mortar-sand ratio of the material.
[0114] Comparative Examples 1 to 6
[0115] The raw material compositions and contents of the cement-based self-leveling materials based on fully recycled sand powder from shield slag in Comparative Examples 1 to 6 are different. The specific formulas are shown in Table 6:
[0116] Table 6: Raw material formula of cement-based self-leveling material based on fully recycled sand powder from shield slag (parts by mass)
[0117]
[0118]
[0119] Note: The retarder in the table is sodium gluconate (model: q162sxw005).
[0120] According to the formula in Table 6, the preparation method and construction steps of cement-based self-leveling materials based on fully recovered sand powder from shield waste in Comparative Examples 1 to 6 are consistent with those in Example 4, and the mixed water content during the construction process of Comparative Examples 1 to 6 is 490, 490, 420, 350, 350, 385, 399, and 399 parts by mass, respectively.
[0121] Test Example 2: Construction Performance Test of Cement-Based Self-Leveling Materials with Fully Recycled Sand Powder from Shield Mine Slag in Comparative Examples 1 to 8
[0122] The construction performance of the cement-based self-leveling material with fully recycled sand powder from shield slag prepared in Comparative Examples 1 to 6 was tested. The specific test indicators and methods were consistent with those in Test Example 1. The experimental results are shown in Table 7:
[0123] Table 7: Construction performance test results of cement-based self-leveling materials with fully recycled sand powder from shield slag prepared in Comparative Examples 1 to 6
[0124]
[0125] It can be seen from the construction performance test results in Table 7 that the self-leveling materials based on fully recycled sand powder prepared in Comparative Examples 1 to 6 have poorer performance than Examples 1 to 4. The main reasons are: No water reducer is added to Comparative Example 1, and even if the water-cement ratio is high, the fluidity is lower than the requirement; after adjustment, 0.2% of water reducer is added to Comparative Example 2, but segregation problem occurs again; after further adjustment, cellulose ether thickener is added to Comparative Examples 3 to 5, and the dosage of water reducer and thickener is adjusted considering the synergistic effect of thickener and water reducer, and the amount of water added is adjusted until the fluidity of the self-leveling slurry meets the specification requirements and no segregation occurs, but Comparative Examples 4 to 5 are to ensure that 2 The fluidity at 0min meets the specification requirements. Compared with Example 1, no accelerator or expansion agent is added, but a retarder is added, resulting in the first day flexural and compressive strengths failing to meet the specification requirements, and due to the low amount of glue powder, the tensile bond strength also fails to meet the specification requirements; in view of this, 0.3% of accelerator is added to Comparative Example 6, thereby, the loss of fluidity at 20min is not large, and the compressive and flexural strengths at 1d also meet the specification requirements, but the glue powder content of Comparative Example 6 is lower than that of the embodiment, the tensile bond strength does not meet the specification requirements, and no expansion agent is added, and the mortar-sand ratio is also higher than that of Example 2, so the 28d dimensional change rate does not meet the specification requirements.
[0126] Comparative Example 7
[0127] The difference between this comparative example and Example 1 lies in the different parameters of recovered sand powder. The preparation process of the recovered sand powder in this comparative example is basically the same as that in Example 1, except that the sieving particle size in step (3) is different. The parameters of the recovered sand powder obtained in this comparative example are: mud content ≤10%, the particle size range of the recovered sand powder is 0.25-0.5 mm, and the mass proportion of the recovered sand powder below 0.35 mm is ≥80%.
[0128] The composition and addition amount of other raw materials are consistent, and the preparation method and construction method are also the same.
[0129] Comparative Example 8
[0130] The difference between this comparative example and Example 1 is that the accelerator is replaced by an equal amount of retarder (the ingredient is sodium gluconate, model number is q162sxw005), the other raw material compositions and addition amounts are the same, and the preparation method and construction method are also the same.
[0131] Comparative Example 9
[0132] The difference between this comparative example and Example 1 is that the water reducing agent is 0.7 parts by mass, the cellulose ether is 3.5 parts by mass, and the other raw material compositions and addition amounts are the same, and the preparation method and construction method are also the same.
[0133] Comparative Example 10
[0134] The difference between this comparative example and Example 1 is that the water reducing agent is 3.5 parts by mass, the cellulose ether is 0.7 parts by mass, and the other raw material compositions and addition amounts are the same, and the preparation method and construction method are also the same.
[0135] Comparative Example 11
[0136] The difference between this comparative example and Example 1 is that the rubber powder is 7 parts by mass, and the mass parts are supplemented by recycled sand powder. The composition and addition amount of other raw materials are consistent, and the preparation method and construction method are also the same.
[0137] Comparative Example 12
[0138] The difference between this comparative example and Example 1 is that the rubber powder is 25 parts by mass, the recovered sand powder is 689 parts by mass, and the other raw material compositions and addition amounts are consistent, and the preparation method and construction method are also the same.
[0139] Test Example 3: Comparative Examples 7 to 12: Construction Performance Test of Cement-Based Self-Leveling Materials with Fully Recycled Sand Powder from Shield Mine Slag
[0140] The construction performance of the cement-based self-leveling material with fully recycled sand powder from shield slag prepared in Comparative Examples 7 to 12 was tested. The specific test indicators and methods were consistent with those in Test Example 1. The experimental results are shown in Table 8:
[0141] Table 8: Construction performance test results of cement-based self-leveling materials with fully recycled sand powder from shield slag prepared in Comparative Examples 7 to 12
[0142]
[0143] It can be seen from the results in Table 8 that the performance of the cement-based self-leveling materials prepared in Comparative Examples 7 to 12 after construction is significantly reduced compared with Example 1, especially when the particle size of the prepared recycled sand powder is larger, the fluidity of the obtained material is significantly weakened, and the self-leveling property is significantly reduced; when the raw material does not contain a coagulant, it will seriously cause the flexural and compressive strengths to fail to meet the specification requirements; when the amount of water reducer and cellulose ether added in the raw material exceeds the appropriate range, the material is prone to segregation problems and affects the fluidity and flexural and compressive strength of the material; in addition, when the rubber powder in the raw material exceeds the appropriate range, it has a greater impact on the tensile bonding strength of the material, and at the same time, it will also affect the flexural and compressive strength of the material to a certain extent.
[0144] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A cement-based self-leveling material based on fully recycled sand powder from shield slag, characterized in that: Calculated by weight, the raw materials of the cement-based self-leveling material include 470-510 parts of cement, 130-160 parts of fly ash, 10-30 parts of silica fume, 1-3 parts of water reducer, 1-3 parts of cellulose ether, 10-20 parts of glue powder, 1-3 parts of accelerator and 600-800 parts of recycled sand powder.
2. The cement-based self-leveling material based on fully recovered sand powder from shield slag according to claim 1 is characterized in that: The particle size range of the recovered sand powder is 0.075-2.36 mm, and the mud content of the recovered sand powder is ≤10%.
3. The cement-based self-leveling material based on fully recovered sand powder from shield slag according to claim 2 is characterized in that: The mass proportion of the recovered sand powder below 0.15 mm in the recovered sand powder is ≥ 65%.
4. The cement-based self-leveling material based on fully recovered sand powder from shield slag according to claim 1 is characterized in that: The cement is silicate cement, and the cement grade is not less than 42.5R; the fly ash is grade II fly ash; the silica ash grade is not less than SF92; the water reducer is a polycarboxylate water reducer; the cellulose ether is hydroxypropyl methylcellulose; the rubber powder is a redispersible latex powder; and the accelerator is selected from one or more of lithium carbonate, lithium hydroxide, lithium chloride, aluminum sulfate, and sodium aluminate.
5. The cement-based self-leveling material based on fully recovered sand powder from shield slag according to claim 1 is characterized in that: The raw materials of the cement-based self-leveling material also include an expansion agent and a defoaming agent.
6. The cement-based self-leveling material based on fully recovered sand powder from shield slag according to claim 5 is characterized in that: In terms of mass fraction, the swelling agent is 0.1 to 50 parts, and the defoaming agent is 0.1 to 1 part.
7. The cement-based self-leveling material based on fully recovered sand powder from shield slag according to claim 5 is characterized in that: The expansion agent is selected from one or more of plastic expansion agent, calcium sulfoaluminate, calcium oxide, and magnesium oxide; and the defoamer is a polyether defoamer.
8. The cement-based self-leveling material based on fully recovered sand powder from shield slag according to any one of claims 1 to 7, characterized in that: The recycled sand powder comes from shield slag and residual mud at the rail transit construction site, and the preparation steps include: (1) Remove large stones, metal impurities and fine sand from the shield slag and mud at the rail transit construction site by washing and screening, and then perform coarse screening to remove organic impurities and isolated stones; (2) washing the shield slag screened in step (1) with water, and controlling the washing time according to the mud content of the shield slag, so that the surface of the sand powder at the discharge port is relatively clean and has no obvious mud marks; (3) drying the sand powder after washing in step (2) to a moisture content of less than 10% to obtain good dispersibility; (4) The sand powder dried in step (3) is sieved, and the aperture of the sieve is 2.36 mm, and the sand powder obtained is the recovered sand powder.
9. A method for preparing the cement-based self-leveling material based on fully recovered sand powder from shield slag as claimed in any one of claims 1 to 8, characterized in that: The preparation steps include: S1. Mix and stir the raw materials except the recycled sand powder according to the proportion, and the stirring time is 1 to 2 minutes; S2. Then, the recovered sand powder is added to step S1 and stirred for 4 to 6 minutes to obtain a cement-based self-leveling material based on fully recovered sand powder from shield slag.
10. Application of cement-based self-leveling material based on fully recycled sand powder from shield slag, characterized in that: The cement-based self-leveling material based on fully recycled sand powder from shield slag as claimed in any one of claims 1 to 8 is mixed and stirred with water in a mass ratio of (1400-1800): (380-420) and then constructed.
Citation Information
Patent Citations
Self-leveling mortar with fly ash as main raw material
CN111875318A
Single-liquid and double-liquid switchable slurry for synchronous grouting of shield tunnel
CN114853435A